Physicochemical properties and filling capacity of an experimental iodoform-based paste in primary teeth - Renata Pereira de Samuel MARQUES; Cacio MOURA-NETTO; Natalia Matsuda de OLIVEIRA; Carmela Rampazzo BRESOLIN; Anna Carolina Volpi MELLO-MOURA; Fausto Medeiros MENDES; Tatiane Fernandes NOVAES (Sociedade Brasileira de Pesquisa Odontológica, 2020)
Abstract In this study, we evaluated the physicochemical properties (PCP; radiopacity, flow, pH, and solubility) and the quality of root canal filling provided by an experimental industrialized paste (EP), with the same active ingredients as those of the Guedes Pinto paste, compared with the Vitapex® paste. PCP were analyzed according to the ANSI/ADA laboratory testing methods for endodontic filling and sealing materials. To analyze filling capacity, 120 artificial primary teeth (60 maxillary incisors [MIs] and 60 mandibulary molars [MMs]) were endodontically treated. The teeth were divided into eight groups based on the dental group (MIs or MMs), filling material (Vitapex® or EP), and insertion method (syringe or lentulo). The Image J® software was used to analyze the initial an final digital radiographies of each tooth, measuring and comparing root canal and void areas. The percentage of filling failure areas was obtained. Data were submitted to ANOVA and Tukey test of mean comparison. Regarding PCP, both pastes presented results according the ANSI/ADA standards. Flow capacity: Vitapex: 19.6 mm, EP: 25 mm (p < 0.01); radiopacity: Vitapex: 4.47 mmAl, EP: 6.06 mmAl (p < 0.01); pH after 28 days: Vitapex: 7.79, EP: 8.19 (p = 0.12); and solubility after 28 days: Vitapex: 2.68%, EP: 2.89% (p > 0.05). Regarding filling capacity analysis, EP demonstrated 12.5% of failure against 31.5% of Vitapex (p < 0.01). Compared to Vitapex, EP presented statistically significantly better results in flow, radiopacity, pH, and filling capacity. Molars presented more filling failures than incisors. The insertion method using a syringe and a thin tip was significantly better than that using Lentulo spiral carriers.